Simulation of Frequency Converters Operation in Industrial Power Net - Svinkunas, G.; Medvedev, K. (Elektronika ir Elektrotechnika, 2012)
Frequency converters, used for induction motors regulation, cause higher voltage harmonic in power net. Level of harmonic depends upon inverter and power net parameters; sometimes power net parameters make more influence for electric energy quality than frequency converter parameters. In this research some models of frequency converters were analyzed, comparing simulation results each with other and with real converter voltages and currents measurement results. Analysis of voltage harmonics in power nets with frequency inverters was done in this article, analyzing influence of power net parameters to power quality. Ill. 14, bibl. 7, tabl. 2 (in English; abstracts in English and Lithuanian). DOI: http://dx.doi.org/10.5755/j01.eee.117.1.1055